Evaluating the Impact of Leadership Strategies on the Development of Learning Organizations - Kasmalinda; Niswanto; Ismail (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study examines the impact of transformational and distributed leadership on fostering learning organizations within Sukma Bangsa School. Transformational leadership is anticipated to drive positive changes by enhancing staff motivation and engagement, while distributed leadership emphasizes shared responsibility and collaborative efforts to sustain a progressive learning environment. Employing a quantitative survey approach, data was collected from 150 respondents, including teachers, school principals, and administrative staff, using a Likert scale-based questionnaire. Data analysis involved descriptive statistics, Pearson correlation, and linear regression tests to evaluate the influence of these leadership styles on organizational learning. Findings reveal that transformational leadership holds a significant positive correlation (r = 0.78) with organizational learning, with an average rating of 4.3. Distributed leadership also shows a substantial effect, with a regression coefficient of β = 0.64, indicating that the collaborative division of responsibilities enhances staff involvement and professional collaboration. In summary, both leadership styles significantly contribute to the advancement of learning organizations in schools, promoting a culture of collaboration and innovation, though some resistance to change persists. This research highlights critical implications for school management in strengthening leadership roles to boost organizational learning effectiveness.